Hospice care for patients with end-stage disease (终末期患者的安宁疗护对策) - XI Wen (奚汶) (Journal of International Translational Medicine Limited, 2024)
Hospice care is a humanized nursing service approach that establishes trust with patients through communication skills. It adopts active and effective psychological intervention methods based on the psychological characteristics of end-of-life patients at different stages to alleviate their pain and fear of death. It helps patients establish the best psychological state during the final treatment process, improve their quality of life, and alleviate the grief of their families. The implementation of palliative care methods for end-stage patients with psychological states is beneficial for improving their psychological status, in order to achieve the goal of ensuring that the deceased are as good as the living, and is worthy of clinical promotion. (安宁疗护是一种人性化的护理服务方式, 通过沟通技巧与患者建立信任关系, 并根据临终患者不同时期的心理特点, 采取积极、有效的心理干预方法, 缓解终末期患者生理上的痛苦和面对死亡的恐惧心理, 帮助患者在最后的治疗过程中建立最佳的心理状态, 提高生活质量, 同时减轻患者家属的悲痛。本研究就终末期患者的安宁疗护对策进行总结分析, 旨在为提高终末期患者的生存质量提供参考。)